Cleistanthus collinus' lignan extract was extracted using the optimal solvent, volume, and time. - LAVANYA,; Dr. Kiran, (The journal of contemporary issues in business and government, 2017)
In order to acquire and preserve herbarium specimens, Cleistanthus collinus need additional precautions for their protection. Aryl naphthalene is found in plants and has a wide range of physiological effects. A soxhlet extractor is being used to study the extraction of lignan-derived compounds from plants. Alcoholic extract and defated petroleum ether are efficient solvents because they are optimised for polarity. Extracting chemicals from plants requires a precise measurement of the solvent volume (1gm per 15 ml). Extraction time for each solvent must be determined.